2019
DOI: 10.1002/nau.23987
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating pelvic floor muscle contractility using two‐dimensional transperineal ultrasonography in patients with pelvic organ prolapse

Abstract: Aim The hiatal anterior‐posterior distance (APD), as measured by two‐dimensional (2D) transperineal ultrasonography, is an indicator of pelvic floor muscle (PFM) contractility. The function of the pelvic floor is independently related to pelvic organ prolapse (POP) severity. However, little evidence concerning the APD for patients with POP before and after PFM training (PFMT) has been published. Therefore, we analyzed 2D transperineal ultrasonography in women with POP. Methods Twenty‐eight women with POP compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The role of pelvic floor muscle training in the prevention and treatment of antenatal and postpartum UI remains a matter of debate. Whereas some studies have found a beneficial effect, others have failed to demonstrate it 26 . Further studies are necessary to better understand the influence of pelvic floor muscle training on postpartum UI prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of pelvic floor muscle training in the prevention and treatment of antenatal and postpartum UI remains a matter of debate. Whereas some studies have found a beneficial effect, others have failed to demonstrate it 26 . Further studies are necessary to better understand the influence of pelvic floor muscle training on postpartum UI prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that only women with SUI had a reduced pelvic floor muscle strength, as shown by a less reduction in LHA under contraction. This suggests that this subgroup may benefit more from pelvic floor training 26 . The role of pelvic floor muscle training in the prevention and treatment of antenatal and postpartum UI remains a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…The pelvic floor muscles can be protected if women perform the PFMT during pregnancy, and, it has a significant effect on preventing the injury of levator ani muscle. The size of the hiatus of levator ani muscle is related to the symptoms and signs of POP (Dietz et al 2008), so it can be used as an anatomical alternative indicator for evaluating PFM function (Ouchi et al 2019). The area of hiatus of levator ani muscle is bounded by pubic muscle, symphysis pubis and inferior branch of pubis.…”
Section: The Effect Of Pelvic Floor Muscles Training On Pelvic Floor Dysfunction During Pregnancymentioning
confidence: 99%